Full-Thickness Facial Pressure Injury and Buried Dentition from Prone Positioning in a Patient with COVID-19. (August 2021) - Conlon, Christopher; Slovacek, Cedar; Jalalabadi, Faryan; Winocour, Sebastian; Olorunnipa, Olushola
Abstract : ABSTRACT: Prone positioning is recognized for its efficacy in the treatment of acute respiratory distress syndrome related to COVID-19. Here the authors present a case of a facial pressure injury and buried dentition that occurred as a result of prolonged prone positioning in a patient who was COVID-19 positive. The patient was treated with primary closure of the injury and pressure offloading.